Health education strategies for pregnant and puerperal women in coping with the COVID-19 pandemic (Research, Society and Development, 2021)
Objective: to list health education strategies aimed at pregnant women and puerperal women in the context of the pandemic by COVID-19. Method: Integrative literature review carried out through the Medline, Cinahl and Lilacs databases using the crossing of the descriptors "Coronavirus infections", "Health Education" and "Pregnant Women" and their analogues in Portuguese and Spanish. The selection process of the articles considered the recommendations of the Preferred Reporting Items for Systematic Reviews and Meta-Analyses. 402 articles were found, among which seven addressed the proposed theme and were selected to compose the final sample of this study. Results: The COVID-19 pandemic imposed measures to contain new cases resulting in social isolation. These changes contributed to the media becoming privileged places for exchanging information. Educational and health institutions and health professionals used social networks (Instagram®, Facebook® and WhatsApp®), radio stations and “lives” to disseminate and address themes related to pregnancy, the puerperium and the new coronavirus. The main topics addressed were care with breastfeeding, prevention, flow of care for pregnant women and postpartum women with COVID-19 and preparation for delivery. Conclusion: The media and social networks allowed pregnant women and mothers to have access to safe information based on the recent scientific evidence on COVID-19, bringing to light a new format of educational strategy and contributing to the prevention of emerging disease and health promotion for women. women.